PENERAPAN METODE INQUIRI DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPLANASI SDN NURUL JIHAT DESA PEMEPEK - Handayani, Suci; Fazalani, Runi; Mayanti, Ely; Pertiwi, Santhi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this study was to improve the quality of the process and learning outcomes of writing explanatory texts at SDN Nurul Jihat Pemepek Village using the inquiry method. The method used is quantitative research that leads to class action. The techniques used in this study through tests, observation and documentation. In this study, the application of the inquiry method can improve the ability to write explanatory texts using the inquiry method in class VI students at SDN Nurul Jihat Pemepek Village, Indonesia in the 2022/2023 academic year. Learning outcomes were marked by an increase in the number of students who reached the mastery limit in the ability to write process explanation texts, namely (a) in the first cycle of 60.39%, (b) in the second cycle the learning mastery results were obtained by 71.42%, and (c ) in cycle III the results of learning completeness were 79.75%.